The History of Psychotherapy in Rumania during the Socialist Dictatorship of Nicolae Ceauşescu (European Journal of Mental Health, 2012)
The paper tries to provide a history of psychotherapy in Rumania during the socialist dictatorship of Nicolae Ceauşescu (1965–1989). In order to fully understand the peculiarities of the development of psychotherapy in the last decades of the previous century, it is absolutely necessary to take into consideration the deep degradation of the quality of interpersonal relations in Rumania and to analyze the causes that have determined this process. Rumania is the only country in Eastern Europe having as leaders, for 45 years continuously, two Stalinists, both of them with identical political formation, who are remembered for intense ideological activity, misguided zeal and constancy, both becoming dreaded and indisputable leaders, setting up a national-communist dictatorship – Gheorghe Gheorghiu-Dej, and a personal one – Nicolae Ceauşescu. Under these circumstances, beginning with 1945, the recently founded Rumanian Society for Psychopathology and Psychotherapy disrupted its activity, due to the schisms between members. The Rumanian Academy was abolished, and a new one was set up. One by one, the Popular Rumanian Academy contested Freudism, psychosomatic medicine, and behaviourism. Without being formally forbidden, psychotherapy was incompatible with the primitive Marxism of the era, and this general state of things lasted for quite a long period. The paper presents the efforts of specialists after the 60s, when more papers and books were published that described various types of psychotherapies, familiarising the professionals with the fundamental ideas in psychotherapy; there were also psychiatrists and psychologists with initiatives in the field and the main textbooks published in this period described psychotherapeutic methods. Unfortunately, little attention was paid to psychoanalysis, cognitive therapies, group therapies, family therapies, and psychodrama. Without openly suppressing the practice of psychotherapy, the officials responsible for the health system did not encourage the ones with such initiatives at all, and the academic bodies, with few exceptions, were hostile to various forms of psychotherapy with an emphasis on those of psychoanalytic origin, for which they had cultivated old refl exes of rejection. This state of things explains the amplitude and the vigour of the initiatives breaking out after 1989, accomplishing the modalities for a structured and complete training.